2020
DOI: 10.21203/rs.2.20450/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Outcome impact of individualized fluid management during spine surgery A before-after prospective comparison study

Abstract: Background: Individualized fluid management (IFM) has been shown to be useful to improve the postoperative outcome of patients undergoing major abdominal surgery. A limited number of clinical studies have been done in orthopaedic patients and have yielded conflicting results. We designed the present study to investigate the clinical impact of IFM in patients undergoing major spine surgery. Methods: This is a before-after study done in 300 patients undergoing posterior spine arthrodesis. Postoperative outcomes … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
(29 reference statements)
0
1
0
Order By: Relevance
“…Our study correlates well with previous studies by Bacchin et al and Che et al who found that patients who received GDFT in spine surgery had similar duration of hospital stay as compared with controls despite fewer postoperative complications and lesser duration of ICU stay. 13,14 In our study, we included only ASA physical status I and II patients. Our results are consistent with previous studies which have shown that outcome benefits related to the use of intraoperative GDFT are not limited to high-risk patients.…”
Section: Discussionmentioning
confidence: 99%
“…Our study correlates well with previous studies by Bacchin et al and Che et al who found that patients who received GDFT in spine surgery had similar duration of hospital stay as compared with controls despite fewer postoperative complications and lesser duration of ICU stay. 13,14 In our study, we included only ASA physical status I and II patients. Our results are consistent with previous studies which have shown that outcome benefits related to the use of intraoperative GDFT are not limited to high-risk patients.…”
Section: Discussionmentioning
confidence: 99%